The essence and sources of opportunism in business activity - Rudolf, Stanisław (Publishing House of Wroclaw University of Economics and Business, 2021)
As observed in recent years, the increased interest in the problem of opportunism in business activity is mainly attributable to the new institutional economics, according to which limiting this phenomenon has become the basic means of reducing transaction costs, and consequently also improving efficiency. The relations between opportunism and transaction costs are discussed in this study, which also addresses the very essence of opportunism, but the author’s attention was mainly focused on the sources of opportunism. The most important ones, namely specific assets and turbulent environment, were analysed in detail. The purpose of the article was to determine how and to what extent these sources contribute to the opportunistic behaviour displayed by parties to a transaction. The author also described the relations between specific assets and a turbulent environment.
Argumenta Oeconomica, 2021, Nr 2 (47), s. 5-18
Keywords: opportunism; specific assets; turbulent environment; transaction costs